2019
DOI: 10.1016/j.hrthm.2018.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Structural remodeling and conduction velocity dynamics in the human left atrium: Relationship with reentrant mechanisms sustaining atrial fibrillation

Abstract: CV dynamics are determined largely by the extent of remodeling. Rate-dependent CV slowing sites are predominantly confined to LVZs (0.2-0.5 mV), and the resultant CV heterogeneity may promote driver formation in AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 28 publications
6
32
0
Order By: Relevance
“…This study has shown that ESA were predominantly mapped to LVZs and that the proportion of LVZs strongly correlated to the number of ESA identified. These findings are supported by sites of structural remodeling resulting in alteration in CV dynamics that promote reentrant mechanisms 26,27 and that reentrant activity anchors to sites of structural heterogeneity 28 . The bipolar voltage map can thereby be used by the operator to plan the extent of their ablation.…”
Section: Discussionmentioning
confidence: 83%
“…This study has shown that ESA were predominantly mapped to LVZs and that the proportion of LVZs strongly correlated to the number of ESA identified. These findings are supported by sites of structural remodeling resulting in alteration in CV dynamics that promote reentrant mechanisms 26,27 and that reentrant activity anchors to sites of structural heterogeneity 28 . The bipolar voltage map can thereby be used by the operator to plan the extent of their ablation.…”
Section: Discussionmentioning
confidence: 83%
“…It has been established that CV varies in areas of non‐low voltage zones (LVZs) compared to LVZs. It has also been shown that CV has a negative correlation between bipolar voltage and proportion of non‐LVZs . CVs of 1.59 and 0.98 m/s were used depending on the proportion of non‐LVZs and LVZs that was present, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It has also been shown that CV has a negative correlation between bipolar voltage and proportion of non-LVZs. 7,8 CVs of 1.59 and 0.98 m/s 7,8 were used depending on the proportion of non-LVZs and LVZs that was present, respectively. In vitro study HL1 cells which are immortal murine cardiac atrial cell lines (Sigma-Aldrich Inc, NM) were used for the in vitro study.…”
Section: Activation Times and Pole Leadersmentioning
confidence: 99%
“…Re-entry anchor location and driver formation may also depend on electrophysiology, conduction velocity dynamics, cardiac wavelength and anisotropy. 52,[121][122][123][124] approach that aims to streamline activation patterns. 127 Roney et al…”
Section: Differentiating Between Mechanisms Using Limited Data and Inmentioning
confidence: 99%